Guidelines for the control of narcotic and psychotropic substances : in the context of the international treaties - Rexed, Bror, 1923-2023; Edmondson, K.; Khan, Inayat, Hazrat, 1882-1927; Samson, Robert J. (Geneva : World Health Organization, 1984)
Stand van zaken wat betreft de geneesmiddelenmarkt: in hoeverre is deze beschermd tegen bijvoorbeeld verslaving.